(untitled) - Linden, Guy (Boca Raton, FL, 1999)
his authoritative text provides the food industry professional with a guide to the range of intermediate food products, their functionality, methods of manufacture and applications. The first part of the book looks at the development of IFPs, common functional properties and methods of extraction and purification. It then covers IFPs derived from plants, milk, eggs, meat and fish. IFPs from by-products such as whey and blood are also discussed
Keywords: Food,Thực phẩm; Composition,Thành phần